THE EXISTENCE OF “NGINANG” AS A SOCIAL AND THEOLOGICAL STUDY OF PUPPETRY IN BALI - Widnyana, I Kadek; Sadevi, Luh Wina; Widyarto, Rinto; Shahab, Fauziah; Putra, Ida Bagus Hari Kayana (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Nginang is the habit of chewing betel leaves and other herbs, such as lime, gambier, areca nut, and tobacco. Nginang has been practiced by people in Southeast Asian countries and parts of Southern China since the 15th century AD. Currently, nginang habit in Indonesia has decreased, which can be caused by many factors. The custom of nginang in Indonesia, especially in Bali, has meaning in various rituals, such as in Balinese puppetry. Nginang functions as a social and theological means of Balinese Dharma Pewayangan Bali. The purpose of this study is to explore the social-theological meaning and existence of the nginang custom for puppeteer in Bali. This is a qualitative study, where primary data is obtained through interviews and observations, while secondary data is obtained through literature review. The conclusion from this study is that nginang is a theological symbol that unites spiritual and social aspects in the life of Balinese puppeteers who must master various arts and the Dharma of Balinese puppetry. Nginang can control words, actions, peace, and harmony during the performance and daily life of the dalang. Nginang should continue to the young generations of puppeteers in order to master the various arts and Dharma of Balinese puppetry.